Organizational Affective Tone: A Meso Perspective on the Origins and Effects of Consistent Affect in Organizations - Knight, Andrew P.; Menges, Jochen I.; Bruch, Heike (Academy of Management Journal, 2018)
Grounded in an open systems perspective, we build and test new theory about how the kinds of industries in which an organization participates influence organizational affective tone and connect to workforce strain. We propose that the more an organization’s activities lie in consumer-centric industries (e.g., service, retail), the more positive and less negative the organization’s affective tone. We connect consumer-centric industry participation and affective tone by explaining how personnel policies and organizational structure generate and sustain consistent positive and negative affect throughout an organization. Additionally, we examine the effects of organizational affective tone on workforce strain. The results of a survey-based study of 24,015 human resource managers, top management team members, and employees of 161 firms largely support our predictions. We discuss the implications of considering macro contextual factors for understanding affect in organizations.